Unveiling the Entrepreneurial Journey: Lived Experiences of Filipino Women Entrepreneurs - Cabrera, Julianne F.; Flores, Jeraldine B.; Lualhati, Genalyn P.; Hernandez, Edna M. (Community and Social Development Journal, 2025)
Women entrepreneurs play a crucial role in driving economic growth and innovation. This study explored the lived experiences of Filipino entrepreneurs, specifically, determined their experience, identified the challenges they faced, and proposed relevant follow-up extension activities. A phenomenological design using a qualitative approach was employed. Data were gathered through semi-structured interviews with three recipients of the livelihood package provided by the college. The findings revealed that the entrepreneurs' experiences significantly impacted their personal, social, and economic lives, and they encountered various challenges in their businesses. The study suggested the need for appropriate follow-up extension activities to help recipients overcome these barriers. Key recommendations include conducting seminars, workshops, or training programs to equip entrepreneurs with new knowledge and skills for effective business management; seeking sponsorship from the Local Government Unit for extension service programs to support entrepreneurs in addressing personal, social, and economic challenges; implementing monthly observations and evaluations by the college’s Extension Services office to ensure the sustainability of extension service projects; and encouraging future research to further investigate other entrepreneurial experiences that may impact business success.